2008
DOI: 10.1039/b717431d
|View full text |Cite
|
Sign up to set email alerts
|

Non-cytotoxic polymer vesicles for rapid and efficient intracellular delivery

Abstract: We have recently achieved efficient cytosolic delivery by using pH-sensitive poly(2-(methacryloyloxy)ethylphosphorylcholine)-co-poly(2-(diisopropylamino)ethylmethacrylate) (PMPC-PDPA) diblock copolymers that self-assemble to form vesicles, known as polymersomes, in aqueous solution. It is particularly noteworthy that these diblock copolymers form stable polymersomes at physiological pH but rapidly dissociate below pH 6 to give molecularly-dissolved copolymer chains (unimers). These PMPC-PDPA polymersomes are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
215
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(224 citation statements)
references
References 44 publications
9
215
0
Order By: Relevance
“…[125] Vesicles with responses to pH stimulus also exhibit applications for the rapid and non-cytotoxic cellular delivery of DNA sequences, which opens the possibilities for efficient gene-delivery for the treatment of specific genetic diseases. [100,101] The use of polymer vesicles as synthetic nano-reactors [140] has also been reported with several biological connotations. [137] Vesicles that can successfully convert ADP into the biochemical fuel ATP have been prepared, [135] alongside multi-step cascade reactions that utilize vesicles with three different incorporated enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[125] Vesicles with responses to pH stimulus also exhibit applications for the rapid and non-cytotoxic cellular delivery of DNA sequences, which opens the possibilities for efficient gene-delivery for the treatment of specific genetic diseases. [100,101] The use of polymer vesicles as synthetic nano-reactors [140] has also been reported with several biological connotations. [137] Vesicles that can successfully convert ADP into the biochemical fuel ATP have been prepared, [135] alongside multi-step cascade reactions that utilize vesicles with three different incorporated enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…[99] The use of these highly biocompatible PMPC-PDPA copolymer vesicles as non-toxic synthetic vectors for the in vitro delivery of either DNA or dye molecules to living cells has been demonstrated. [100,101] DNA-loaded PMPC-PDPA vesicles undergo rapid endocytosis and the lower local pH within the endocytic organelle (pH 5-6) causes protonation of the hydrophobic PDPA chains, vesicle dissociation, and hence triggered release of the payload. High transfection efficiencies have been demonstrated using Human Dermal Fibroblast (HDF) cell lines for these delivery vehicles.…”
Section: Reactive and Environmentally Responsive Membranes For Delivementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly Ahmed and coworkers have shown that the endocytic degradative environment can favor cytosolic delivery using hydrolyzable polymersomes (Ahmed et al 2006;Kim et al 2009). pH-sensitive polymersomes have also been proposed by the Battaglia group using poly(2-[diisopropylamino] ethyl methacrylate) (PDPA) (Lomas et al 2007(Lomas et al , 2008Massignani et al 2010). At physiological pH, PDPA copolymers aggregate to form stable vesicles that can encapsulate several molecules and macromolecules (Lomas et al 2007(Lomas et al , 2008Massignani et al 2010).…”
Section: Endosome Escape Strategiesmentioning
confidence: 99%
“…These synthetic alternatives to lipid vesicles can be designed to undergo controlled disassembly as a function of several external stimuli to release their cargo. Typical examples of release-triggering stimuli are temperature (Qin et al 2006), light (Robbins et al 2009), ultrasound and magnetic field (Meng et al 2009), redox conditions (Cerritelli et al 2007), enzymatic cleavage (Ahmed and Discher 2004), and, most relevant, pH (Du et al 2005;Ahmed et al 2006;Lomas et al 2008;Qiu et al 2010). Cerritelli et al (2007) have shown that using a protease-sensitive sulfur bridge polymersome, cytosolic delivery can be achieved.…”
Section: Endosome Escape Strategiesmentioning
confidence: 99%